2020
DOI: 10.34172/ipp.2021.25
|View full text |Cite
|
Sign up to set email alerts
|

High risk individuals in COVID-19 pandemic; an updated review

Abstract: In December 2019, cases of pneumonia with an unknown pathogen were reporting in Wuhan city, China. The World Health Organization (WHO) recognized it as a pandemic, on March 11, 2020. The most frequent site of involvement is the respiratory system. The most common symptoms include cough, fatigue and fever. In some cases, neurological, respiratory and gastrointestinal complications can lead to death. Inflammatory cytokines can play a major role in pathogen damage. Due to the pandemic of COVID-19 and its severe c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…It has been observed that obese patients have higher mortality in COVID-19 infection than non-obese patients. 13,14 Clinicians, no doubt, would like to know if the effect of bromhexine on the risk of mortality varies by obesity status. Is it possible that among obese patients, treatment with bromhexine has a different effect on mortality than in patients who are not obese?…”
Section: Resultsmentioning
confidence: 99%
“…It has been observed that obese patients have higher mortality in COVID-19 infection than non-obese patients. 13,14 Clinicians, no doubt, would like to know if the effect of bromhexine on the risk of mortality varies by obesity status. Is it possible that among obese patients, treatment with bromhexine has a different effect on mortality than in patients who are not obese?…”
Section: Resultsmentioning
confidence: 99%